Assessment of in-vitro Antioxidant/Enzymes Inhibitory Potentials of Aframomum melegueta [Roscoe] K. Schum (Grains of Paradise) Leaf, Stem Bark, Seed Bark and Seed Extracts - Oludare Temitope Osuntokun; V. O. Olumekun; A. O. Ajayi; I. O. Omotuyi; A. Olonisakin (Archives of Current Research International, 2020)
The purpose of this research work is to evaluates the in-vitro antioxidant and antioxidant enzymes inhibition potentials of Aframomum melegueta [Roscoe] K. Schum (Grains of Paradise) Leaf, Stem Bark, Seed Bark and Seed Extracts. Aframomum melegueta is a spice with a similar composition as Ginger, that belongs to the same Zingiberaceae family, used in Nigeria, West Africa and it is used for the treatment of infectious diseases such as urinary tract infections, cancer and diabetes. Antioxidants neutralize the effect of free radicals through different ways and may prevent the body from various diseases. The plant extract were collected from a rain forest in Akugba Akoko, Ondo state, Nigeria. The plant sample was dried, pulverized, filtered with Whatman No 1 filtered paper and the filtrates was concentrated in-vacuum using vacuum rotary evaporator at 40°C and was later concentrated to dryness in a hot-air oven at 40°C. Assessment of antioxidant potentials were performed using Singleton method Total flavonoids (mg/g), Phenol (mg/g), Ferric reducing (FRAP) potentials (mg/g), Free radical scavenging ability (DPPH) (1, 1- diphenyl-2-picryhydrazyl) potentials (%),2,2’-azino-bis(3-ethylbenthiazoline-6-sulphonic acid), 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid (ABTS) scavenging potentials (mMol/g), Fe2+ chelation potentials (%) and OH Radical Scavenging potentials (%) were evaluated. Antioxidant enzymes of plant were assessed using Bentller method, Superoxide Dismutase (SOD) (%), Reduced Glutathione (GSH) (%), Catalase (CAT) and Glutathione Peroxidise (GPX) were evaluated. Seed extract among other extracts of Aframomum melegueta has the highest quantity of flavonoids, Phenol, FRAP, DPPH, ABTS, Fe2+ chelation and OH radical scavenging potential. The leaf extract of A. meleguata has the highest percentage of Superoxide Dismutase (SOD) and Catalase (CAT) while stem bark of Aframomum melegueta has the highest percentage of Reduced Glutathione (GSH) and Glutathione Peroxidise (GPX).it can be deduced from this research work that all parts of the A. melegueta has pharmacological and therapeutic activities judging from literature that A. melegueta can be used to prevent oxidative damage by ROS (Reactive oxygen species) reacting with free radical chelating and catalytic metals which can be used to reduce and prevent various diseases like heart disease, cancer, DNA degeneration, pulmonary and neurological disorder. SOD, GPX, GSH help to control cytokins induced peroxidise level and mediate signal transduction in mammalian cells. It can be deduced that Aframomum melegueta should be the focal point in human diet, natural herbal drug supplement and even in addition to conventional drug to improve the potency and quality of natural drug system. The use of Aframomum melegueta should be encouraged. These results show the potential of Aframomum melegueta as a source of bioactive compounds to be used for pharmaceutical, nutraceutical, and cosmeceutical applications.